Potential Antiaging Effects of DLBS1649, a Centella asiatica Bioactive Extract - Karsono AH; Tandrasasmita OM; Berlian G; Tjandrawinata RR (Dove Medical Press, 2021)
Agung H Karsono,1 Olivia M Tandrasasmita,1 Guntur Berlian,1 Raymond R Tjandrawinata2,3 1Section of Molecular Pharmacology, Research Innovation and Invention, Dexa Laboratories of Biomolecular Sciences, Dexa Medica, Cikarang, West Java 17550, Indonesia; 2Dexa Laboratories of Biomolecular Sciences, Dexa Medica, Cikarang, West Java 17550, Indonesia; 3Faculty of Biotechnology, Atma Jaya Catholic University of Indonesia, Tangerang, 15345, IndonesiaCorrespondence: Raymond R TjandrawinataDexa Laboratories of Biomolecular Sciences, Dexa Medica, Industri Selatan V Block PP 7, Jababeka Industrial Estate II, Cikarang, West Java 17550, IndonesiaTel +62-21-898-41-901Fax +62-21-89841905Email raymond@dexa-medica.comPurpose: Centella asiatica is a traditional medicinal plant, especially for wound healing and as a neuroprotective agent. DLBS1649 is a bioactive extract from C. asiatica, and was studied to investigate its benefits as an antiaging agent.Methods: DLBS1649 was administered to HEK293 and 3T3L1 mammalian cells cultured in a time- or dose-dependent manner. Telomere length analysis was performed. TERT, CMYC, SIRT1, SIRT2, and KL expression were observed using reverse-transcription qPCR. Telomerase protein was studied with ELISA, while calorie restriction was observed using Oil Red O. In vivo study was conducted using Drosophila melanogaster with restricted mean survival time as the statistical method of analysis.Results: DLBS1649 50 μg/mL showed an effect in the prevention of telomere shortening by 50% and decrease in telomerase activity by 28% compared to the controls (70% and 40%, respectively) in the HEK293 cell cultures. TERT-, CMYC-, SIRT1-, SIRT2-, and KL-expression degression was also reduced (29%, 9%, 18%, 25%, 9%, and 30%, respectively) compared to the controls (46%, 40%, 56%, 44%, and 46%, respectively) after ten serial passages. Calorie-restriction activity from DLBS1649 50 μg/mL was seen, with lower fat droplet counts being detected in the treated samples (37%) than the controls (28%) in 3T3L1 cells. DLBS1649 2 mg/mL increased restricted mean survival time in male and female D. melanogaster (23.87% [p< 0.05] and 12.58%, respectively).Conclusion: The results revealed DLBS1649's potential as an antiaging agent based on telomere-length preservation, decreased expression of aging-related genes, increased calorie restriction in vitro, and mortality reduction in D. melanogaster in vivo.Keywords: herbal, TERT, SIRT, klotho, fruit flies, mortality